Financial crisis and income-related inequalities in the universal provision of a public service: the case of healthcare in Spain - Ignacio Abásolo; Marc Saez; Guillem López-Casasnovas (BMC, 2017)
Abstract Background The objective of this paper is to analyse whether the recent recession has altered health care utilisation patterns of different income groups in Spain. Methods Based on information concerning individuals 'income and health care use, along with health need indicators and demographic characteristics (provided by the Spanish National Health Surveys from 2006/07 and 2011/12), econometric models are estimated in two parts (mixed logistic regressions and truncated negative binominal regressions) for each of the public health services studied (family doctor appointments, appointments with specialists, hospitalisations, emergencies and prescription drug use). Results The results show that the principle of universal access to public health provision does not in fact prevent a financial crisis from affecting certain income groups more than others in their utilisation of public health services. Conclusions Specifically, in relative terms the recession has been more detrimental to low-income groups in the cases of specialist appointments and hospitalisations, whereas it has worked to their advantage in the cases of emergency services and family doctor appointments.